Protecting built property against fire disasters: Multi‐attribute decision making with respect to fire risk - Vaidogas, Egidijus Rytas; Šakėnaitė, Jurgita (International Journal of Strategic Property Management, 2010)
The protection of buildings against fire disasters may require a comparison of alternative fire safety designs. The fire safety solutions can be compared by means of a general methodology known as multi‐attribute selection or multi‐criteria decision making. The alternative fire designs can be described by a number of attributes which characterise each of the alternatives. Fire risk expressed in the general form used for the quantitative risk assessment is applied to compose the set of attributes of a multi‐attribute selection problem. It is shown how to accomplish the multi‐attribute selection in the presence of epistemic uncertainties in the elements of fire risk estimate. Epistemic probability distributions assigned to elements of fire risk are specified and propagated though models of the multi‐attribute selection by means of Monte Carlo simulation. An example presented in the paper considers the choice among alternative systems of automatic fire sprinklers. First Published Online: 10 Feb 2011